Perception of the Effects of Working from Home on Isolation and Stress by Spanish Workers during COVID-19 Pandemic - De Andres-Sanchez, Jorge; Belzunegui-Eraso, Angel; Souto-Romero, Mar (Social Sciences, 2023)
This paper tests the explanatory capability of the individual, organizational, environmental and job factors regarding Spanish workers’ perception of isolation and stress owing to working from home (WFH). We used a survey of the Spanish agency Centro de Investigaciones Sociológicas on the Spanish population’s perceptions of several aspects of information technologies that was carried out in March 2021. Information overload, work overload and isolation are perceived to be the principal factors involved in WFH. Because WFH could be inhibit professional development, drawbacks in the infrastructure include overload and impediments to career development as the most relevant variables to explain the perception of isolation. Age and balance between family and work also have explanatory power, but less so for isolation and stress. While people with intermediate ages are less sensitive to isolation and stress, having a correct balance between work and personal life is a protective factor against these effects. From the results in this paper, we outline several questions that must be addressed by labour authorities via legal regulations and by firms and workers to adapt organizational and working culture to ensure the efficient implementation of WFH settings compatible with employees’ well-being.
Keywords: COVID-19 pandemic; home teleworking; isolation; stress; teleworking; working from home; Scopus; Emerging